Science, Colonialism, and Indigenous Peoples : the Cultural Politics of Law and Knowledge. - Whitt, Laurelyn (Cambridge University Press, 2009)
This book examines how contemporary relations between Indigenous and Western nations are shaped by the dynamics of power, the politics of property, and the apologetics of law.